Anaemia of Chronic Kidney Disease: What We Know Now - Anoushka R. Krishnan; Debbie Trinder; Anita C.G. Chua; Aron Chakera; Grant A. Ramm; John K. Olynyk (Journal of Renal and Hepatic Disorders)
Our understanding of the pathophysiology of the anaemia of chronic kidney disease (CKD) has improved considerably in the last decade with the discovery of the iron regulatory peptide hepcidin. Reduced clearance of hepcidin and the presence of a chronic inflammatory state contribute to elevated hepcidin levels in kidney disease. The recent discovery of the various factors and signalling pathways regulating hepcidin has opened up an exciting avenue for research into the development of newer agents that could treat anaemia of CKD. This review highlights our current understanding of iron metabolism in health, the regulators of hepcidin, issues associated with the current available therapies for the treatment of anaemia in CKD and potential novel therapies that could be available in the near future targeting the various factors that regulate hepcidin.